On the redshift of the gamma-ray blazar PKS 0447-439: Optical spectroscopy using Gemini observations with high S/N ratio - Rovero, A.C. (2013)
Abstract: The BL-Lac blazar PKS 0447-439 was detected at very high energy gamma-rays by HESS following the discovery by Fermi-LAT. The lack of both emission and absorption lines in BL-Lacs make the estimation of their redshifts very difficult. Modeling the drop in gamma-ray spectra it was possible to have an estimation of redshift for PKS 0447-439 of z approx 0.2, which is compatible with the value z=0.205 reported by the identification of Ca II absorption lines in optical spectra. By the identification of a weak line of Mg II using spectra with average signal-to-noise S/N approx 80, it has been recently reported a lower limit for the redshift of this blazar of z<=1.246. Triggered by this controversy, we have proposed new optical observations with the Gemini South telescope to perform further spectroscopic analysis with very high S/N ratio (approx 200-500). In this work we present a new optical spectrum of PKS 0447-439, and report on the analysis and results of such observations. Even with this significantly high quality signal we were not able to identify any spectral features to allow an estimation of the redshift. In agreement with other recent studies, we identify the Mg II line reported previously as originated in the Earth´s atmosphere, and conclude the lower limit of the redshift is incorrect. More interestingly, we could not identify the Ca II absorption lines used to report a redshift of 0.205.